População em situação de rua: perspectivas atuais no resgate da cidadania e reinserção social - Pousa Junior, Efren Fernandez (2012)
This dissertation analyzes the issue of social protection of the residents on the street (MSR) considering the possibility of social reintegration and recovery of citizenship of these individuals. Then see how the determinations social, economic, political and cultural, within the contemporary neo-liberal influence in the redefinition of their exclusion. These reflections made on social issues directly involve the idea of breaking what we call a cycle of isolation, lack of formalized production and accumulation of goods and labor. Seeks to deepen the changes in the pattern of coping with the state of poverty, inequality and exclusion, increased by studies on the actions the Federal Constitution of 1988 (social rights and public policies with universalist vision) and other laws under the Constitution, along with an even intense social action organizations (identified in this context, today, quite active early references on poverty in Brazil: a structured ideas of charity and mercy, especially the Catholic Church, in actions that lend themselves to a clear state Social Welfare) Social and Public Policy (now embodied in policies focused in particular on the federal level). It addresses also issues inherently accustomed to civic participation and the attitude of social movements, such as institutional mechanisms to ensure founding principles of freedom and implementing constitutional social rights. It appears, finally, in terms of national analysis, mapping of poverty, inequality and exclusion (2003), drawn from broader concepts of research, showing limitations, advantages and benefits in terms of range of the most reliable real needs social.